The NeXus data format. (1st February 2015) - Könnecke, Mark; Akeroyd, Frederick A.; Bernstein, Herbert J.; Brewster, Aaron S.; Campbell, Stuart I.; Clausen, Björn; Cottrell, Stephen; Hoffmann, Jens Uwe; Jemian, Pete R.; Männicke, David; Osborn, Raymond; Peterson, Peter F.; et al.
<x xml:space="preserve">Abstract</x> NeXus is an effort by an international group of scientists to define a common data exchange and archival format for neutron, X‐ray and muon experiments. NeXus is built on top of the scientific data format HDF5 and adds domain‐specific rules for organizing data within HDF5 files, in addition to a dictionary of well defined domain‐specific field names. The NeXus data format has two purposes. First, it defines a format that can serve as a container for all relevant data associated with a beamline. This is a very important use case. Second, it defines standards in the form of application definitions for the exchange of data between applications. NeXus provides structures for raw experimental data as well as for processed data.